Late-Onset Fahr Disease Presenting with Chronic Vertigo, Right-Sided Postural Instability, and Mild Cognitive Impairment: A Case Report - Dewi Hastuty; Andini Aswar; Mulia Rahmansyah; Diani Nazma; Reza Aditya Digambiro; Hervi Wiranti; Imelda Yunitra (International Journal of Psychology and Health Science, 2026)
Fahr disease, currently recognized within the spectrum of primary familial brain calcification, is a rare neurodegenerative disorder characterized by bilateral intracranial calcifications, most commonly involving the basal ganglia, dentate nuclei, thalamus, internal capsule, and cerebral white matter. It usually presents with movement disorders, neuropsychiatric manifestations, seizures, gait disturbance, or cognitive decline. Chronic vestibular symptoms as the initial manifestation are uncommon and may delay diagnosis, especially in older patients with coexisting vascular brain changes. This report describes a late-onset case of Fahr disease presenting primarily with chronic vertigo, right-sided postural instability, and mild cognitive impairment. Case presentation: A 67-year-old woman presented with chronic spinning vertigo for one year, worsening over the last five months. The symptoms were prominent during positional change from lying to sitting and caused unsteady gait with a sensation of nearly falling. She also reported right-sided pulsatile tinnitus and hearing impairment. Neurological examination showed unidirectional nystagmus with a fast component to the left and right vestibulocochlear nerve dysfunction. Balance assessment revealed consistent right-sided deviation, including positive Romberg test, sharpened Romberg test, Fukuda stepping test, and tandem gait instability. Motor, sensory, autonomic, and limb coordination examinations were within normal limits. Cognitive screening using MoCA-INA showed mild cognitive impairment with a score of 22/30. Laboratory examination showed preserved renal function and normal glucose control, but hypercholesterolemia and elevated LDL cholesterol were present. Brain MRI showed mild periventricular leukoaraiosis, lacunar infarcts in the right cerebellum and left insular region, senile cerebral atrophy, and pathological calcification in the cerebellum and bilateral internal capsule regions, suggestive of bilateral striatopallidodentate calcinosis or Fahr disease. This case highlights chronic vestibular symptoms and right-sided postural instability as an unusual initial presentation of late-onset Fahr disease. Mild cognitive impairment and vascular brain changes may coexist and contribute to clinical severity. Fahr disease should be considered in older patients with persistent vertigo, gait instability, cognitive decline, and bilateral intracranial calcification. Further evaluation of calcium-phosphate metabolism, parathyroid hormone, vitamin D, magnesium, family history, and genetic testing is needed to distinguish primary Fahr disease from secondary Fahr syndrome and to guide long-term management.